DNMT3b-mediated methylation of ZSWIM3 enhances inflammation in alcohol-induced liver injury via regulating TRAF2-mediated NF-κB pathway. Issue 14 (23rd July 2020) - Li, Hai-Di; Chen, Xin; Xu, Jie-Jie; Du, Xiao-Sa; Yang, Yang; Li, Juan-Juan; Yang, Xiao-Juan; Huang, Hui-Min; Li, Xiao-Feng; Wu, Ming-Fei; Zhang, Chong; Zhang, Chao; et al.
Abstract: The regulation of macrophages during inflammatory responses is a crucial process in alcoholic liver disease (ALD) and aberrant macrophage DNA methylation is associated with inflammation. Our preliminary screening results of macrophage methylation in the present study demonstrated the zinc finger SWI2/SNF2 and MuDR (SWIM)-domain containing 3 (ZSWIM3) were hypermethylated in the 5′ untranslated region (5′-UTR) region. ZSWIM3, a novel zinc finger-chelate domain of SWIM, is predicted to function in DNA-binding and protein-binding interactions. Its expression was found to be consistently decreased in macrophages isolated from livers of ethyl alcohol (EtOH)-fed mice and in EtOH+lipopolysaccharide (LPS)-induced RAW264.7 cells. Over-expression of ZSWIM3 was found to attenuate chronic+binge ethanol feeding-induced liver injury and inhibit inflammatory responses in vivo . Enforced expression of ZSWIM3 in vitro was also found to have anti-inflammatory effects. Aberrant expression of ZSWIM3 in alcohol-induced liver injury (ALI) was found to be associated with hypermethylation. Analysis of CpG prediction indicated the presence of two methylated sites in the ZSWIM3 promoter region and methylation inhibitor and DNA methyltransferases (DNMTs)-siRNA transfection were found to restore down-regulated ZSWIM3. Chromatin immunoprecipitation (ChIP) assay and molecular docking affirmed the role of DNMT 3b (DNMT3b) as a principal regulator of ZSWIM3 expression. Mechanistically, ZSWIM3 might affect inflammation by binding with tumor necrosis factor receptor-associated factor 2 (TRAF2), which further mediates the activation of the nuclear transcription factor κB (NF-κB) pathway. The present study, therefore, provides detailed insights into the possible structure and function of ZSWIM3 and thus, contributes new substantial research in the elucidation of the pathogenesis of ALI.